Using Internet Technologies in Legal Practices and Studies in Russia - V.A. Vernigorova (University of Sofia, 2011)
This paper is devoted to the agenda of using computer and Internet technologies in legal practices and studies in Russia. Despite the obvious necessity for professionals to learn English, many graduates in Russia still demonstrate a very poor command of this universal language. And it has become quite impossible for a lawyer (or for any other specialist) to work effectively without using the Internet and for a student - to study and to practice a foreign language.